Conversion of 1D Nb2Se9 Nanowires to 2D Conductive NbSe2 via Hydrogen Annealing: Structural and Electrical Characterization - Lee, Sang Hoon; Lee, Bom; Cho, Sooheon; Kim, Dahoon; Gudena, Gutema Teshome; Kim, Ji Hee; Yu, Hak Ki; Choi, Jae Young (Crystal Growth and Design, 2024)
Van der Waals (vdW) materials, consisting of multiple layers held together by weak vdW forces, have garnered significant interest due to their tunable electronic, optical, and mechanical properties. In this study, a one-dimensional (1D) Nb2Se9 nanowire template, known for its p-type semiconductor characteristics, was synthesized and converted into a conductive NbSe2 nanowire through hydrogen annealing. The conversion process, performed at 300 and 500 °C, maintained the wire morphology and passed through an intermediate NbSe3 phase. Structural analysis confirmed the conversion, showing preferred orientation growth in the vdWs direction [002]. Raman and X-ray diffraction results indicated that residual Se in the material increased interlayer distances and caused stress in the out-of-plane direction. Electrical measurements demonstrated that the converted NbSe2 exhibited metallic properties with linear I-V curves and ohmic contact. The NbSe2 nanowires converted at 300 °C exhibited superior performance, with a breakdown current density of 2.01 MA cm-2, surpassing conventional nano metallic wire materials like Si, Cu, and SnO2. This study highlights the potential of NbSe2 nanowires for applications in nano devices, leveraging their high electrical conductivity and structural integrity maintained at low process temperatures suitable for back-end-of-line (BEOL) processes.
Keywords: Electrical characterization; Hydrogen annealing; Multiple layers; One-dimensional; Optical and mechanical properties; P type semiconductor; Structural characterization; Tunables; Van der Waal; Van der waals' forces